A randomized comparison of gentamicin-clindamycin and cefoxitin-doxycycline in the treatment of acute pelvic inflammatory disease - Walters, M D; Gibbs, R S (Obstetrics and gynecology (New York. 1953), 1990)
In this prospective trial, 130 hospitalized patients with acute pelvic inflammatory disease based on clinical criteria were randomly treated with intravenous gentamicin plus clindamycin (N = 63) or cefoxitin plus doxycycline (N = 67) for at least 4 days, followed by oral clindamycin or doxycycline, respectively, for a total of 14 days. Pre-treatment cultures were obtained for endocervical Neisseria gonorrhoeae and Chlamydia trachomatis, and for endometrial C trachomatis and aerobic and anaerobic bacteria. Overall, 46 subjects (35%) had endocervical cultures positive for N gonorrhoeae. Endocervical and endometrial cultures were positive for C trachomatis in 16 and 6%, respectively. Ninety-five percent of patients had at least one aerobic bacterium, 38% had at least one anaerobic bacterium, and only 2% had no organisms isolated from their endometrium. Fifty-seven subjects taking gentamicin-clindamycin (90.5%) and 64 subjects taking cefoxitin-doxycycline (95.5%) were clinically cured, a nonsignificant difference. Three subjects treated with gentamicin-clindamycin and one treated with cefoxitin-doxycycline required hysterectomy or salpingectomy for cure. Follow-up examinations and cultures were performed in 84% of the subjects. Post-treatment cultures for N gonorrhoeae were negative in all cases tested. Post-treatment endocervical and endometrial C trachomatis cultures were negative in ten of 11 subjects treated with gentamicin-clindamycin and in eight of nine treated with cefoxitin-doxycycline, a nonsignificant difference. We conclude that gentamicin-clindamycin and cefoxitin-doxycycline have similar clinical cure rates for acute pelvic inflammatory disease and are equivalent in eradicating genital N gonorrhoeae and C trachomatis.